Simultaneous and independent control of phase and polarization in terahertz band for functional integration of multiple devices. (July 2022) - Fan, Jiayu; Zhang, Lei; Wu, Zhiyong; Liang, Jiaxuan; Ning, Tingyin; Zhang, Min; Su, Hong; Liang, Huawei
Highlights: Simultaneous and independent control of phase and polarization in terahertz band. Attaining functional integration of multiple THz devices with high efficiencies. Both simulated and experimental results agree very well with the design. Abstract: The control of phase and polarization in terahertz (THz) range is very valuable for wireless communication, biomedicine, and security inspection. Recently, metasurfaces composed of sub-wavelength artificial structures are proposed for the control of THz waves. However, it is still a challenge to realize simultaneous and independent control of the wavefront and polarization distribution in the THz band, although which has been achieved in the optical band by using several metasurfaces. Here, metallic waveguide arrays (MWAs) are proposed to manipulate both the wavefront of two orthogonal polarization components and the phase difference between them so as to attain independent spatial distributions of the phase and polarization direction. By using the compact MWAs, the functional integration of multiple THz devices is attained, including the integration of a lens with a quarter-wave plate, a half-wave plate, and vector beam generators, respectively. The corresponding control efficiency can even be comparable with that of a commercial lens just for THz focusing. The functional integration of multiple devices makes the MWAs very significant in promoting the miniaturization of THz systems and reducing the insertion loss of functional devices, owing to the remarkable decrease of the number and size of required devices.